Cis-regulatory elements operating in the trophoblast - Vcelkova, Terezia; Latos, Paulina A. (Frontiers in Cell and Developmental Biology, 2025)
The placenta is vital for supporting embryonic development and ensuring a successful pregnancy. Its diverse functions are carried out by specialized trophoblast cell types, including the progenitor cytotrophoblast, the multinucleated syncytiotrophoblast, and the invasive extravillous trophoblast. The distinct identities of these cells are governed by tightly regulated gene expression programs, controlled by transcription factors and cis-regulatory elements, particularly enhancers and silencers. They integrate spatiotemporal cues to modulate transcriptional activity and establish cell-type-specific gene expression profiles. Disruptions of these regulatory mechanisms can impair placental development and function, contributing to pregnancy complications. In this review, we explore the interplay between TFs and CREs in trophoblast lineage specification and function, with a focus on enhancers and silencers. We provide an overview of human placental development, describe commonly used in vitro models, and discuss recent technological advances that have deepened our understanding of transcriptional regulation in the placenta.